Hierarchical Sliding Mode Algorithm for Athlete Robot Walking - Van Dong Hai Nguyen; Xuan-Dung Huynh; Minh-Tam Nguyen; Ionel Cristian Vladu; Mircea Ivanescu (Journal of Robotics)
Dynamic equations and the control law for a class of robots with elastic underactuated MIMO system of legs, athlete Robot, are discussed in this paper. The dynamic equations are determined by Euler-Lagrange method. A new method based on hierarchical sliding mode for controlling postures is also introduced. Genetic algorithm is applied to design the oscillator for robot motion. Then, a hierarchical sliding mode controller is implemented to control basic posture of athlete robot stepping. Successful simulation results show the motion of athlete robot.